HOECHST 33258 COMPOUND INTERACTION WITH DIFFERENT GC-CONTENT DNA (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The interaction of Hoechst 33258 (H33258) compound with different GC-content DNA has been studied using the melting method. The obtained data show that at low ionic strengths of the solution (~0.002 M) H33258 does not display specificity for DNA AT sequences. Moreover, the effect was revealed not to depend on DNA nucleotide sequence. It has been shown that the increase in the ionic strength by an order of magnitude results in the development of a pronounced specificity of H33258 for DNA AT-sequences. H33258 was also found to exhibit a higher affinity for DNA having a block structure.
Keywords: GC-content of DNA, Hoechst 33258, minor groove, AT-specificity, melting parameters